IS/IT Master Plan using Ward & Peppard and IS Demand at Department of Agriculture, Food Security and Fisheries, Tasikmalaya Regency - Husaeni, Nurul Azmi; Shofa, Rahmi Nur; Sulastri, Heni (Deparment Information System, Siliwangi University, 2024)
The Tasikmalaya District Agriculture, Food Security and Fisheries Service is an office that has the task of assisting the regent in carrying out regional household affairs in the fields of agriculture, food security and fisheries. The Agriculture, Food Security and Fisheries Service of Tasikmalaya District is an agency that has just merged in the last 3 years as stated in the Tasikmalaya District Regent Regulation Number 59 of 2021. Based on Presidential Regulation Number 3 of 2003 and Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE). So it is necessary to design a master plan for Information Systems and Information Technology using the Ward and Peppard method which consists of input and output stages and adds IS Demand as a tool to identify information system requirements made from an internal business analysis perspective. The results of this research are in the form of an output stage, namely compiling an IS business strategy with the results of 12 proposed information system priorities, an IT strategy with a proposed network infrastructure, and an IS / IT management strategy with a proposal for additional IT fields that support the business processes of the Tasikmalaya District Agriculture, Food Security and Fisheries Service